The association of serum progesterone on day of hCG trigger and IVF outcome - Garg, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A large number of clinical studies have examined the effect of rise in serum progesterone levels on the day of hCG administration in GnRH agonist and antagonist cycle, on pregnancy rates. The mechanisms of this rise in progesterone levels on day of hCG trigger are controversial and also the results of these studies are variable. Methods: This prospectively observational cohort study was conducted from November 2020 to November 2021 at Sarvodaya IVF centre, Delhi. 279 patients completed an IVF/ICSI-ET cycle during the study period and were included in the final analysis. The standard GnRH antagonist (fixed or variable) and long GnRH agonist COS protocols were used. Participants undergoing COS with all gonadotropins were recruited. The study population was subgrouped into two groups according to P4 level on day of hCG trigger (calculated according to ROC curve): Group A (p≤1.5 ng/dl, n=140/279, 50.17%) and Group B (p>1.5 ng/dl, n=139/279,49.82%). Results: The dose of Gonadotropins required, terminal estradiol levels and number of oocytes retrieved were significantly required higher in group B as compared to group A. The percentage of subjects with progesterone rise on the day of hCG trigger were significantly more in agonist protocol (56.1%) as compared to antagonist protocol(43.9%, p<0.001). Pregnancy rate was significantly higher in group A (41.4%,58/114) when compared with group B (29.5%,41/139). The clinical pregnancy rate was also significantly more in group A (50/140,35.7%) as compared to group B (34/139,24.5%) (p=0.041). Conclusions: Patients with higher levels of Progesterone (>1.5 ng/ml) on day of hCG trigger is associated with lower pregnancy rate and clinical pregnancy rates.